2023
DOI: 10.3390/agriculture13030552
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Arbuscular Mycorrhizal Fungi in Mitigating Water Deficit Effects on Durum Wheat (Triticum durum Desf.)

Abstract: Wheat is one of the main staple cereal crops worldwide. However, drought-induced stress is one of the factors limiting wheat productivity, especially in arid and semi-arid regions. The present study aims to investigate the influence of arbuscular mycorrhizal fungi (AMF) on wheat plant growth under water-deficit conditions. Three Algerian durum wheat varieties—Mohamed Ben Bachir (MBB), Boussellem (BS) and Waha (W)—were grown with (+AMF) or without (−AMF) under water-deficit and non-stress conditions. Morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…In the present study, the preventive treatments of T. longibrachiatum, Pseudomonas sp., and those associated with salicylic acid significantly reduced the gray mold and disease severity index on the tomato fruits inoculated with Botrytis cinerea. This is probably due to the ability of this micro-organism to inhibit the enzymatic activity of plants, which decreases the negative effect of the pathogen, as demonstrated in various studies [51,52].…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, the preventive treatments of T. longibrachiatum, Pseudomonas sp., and those associated with salicylic acid significantly reduced the gray mold and disease severity index on the tomato fruits inoculated with Botrytis cinerea. This is probably due to the ability of this micro-organism to inhibit the enzymatic activity of plants, which decreases the negative effect of the pathogen, as demonstrated in various studies [51,52].…”
Section: Discussionmentioning
confidence: 92%
“…Likewise, Amer et al [ 78 ] showed that especially APX and catalase activities significantly decreased after AMF inoculation when water deficit was applied. These authors explained that this probably occurred due to the increased absorption of water provided by AMF hyphae and its transfer to the host plant, decreasing the generation of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) have shown potential for enhancing wheat crop protection through their symbiotic interactions with the plant. When AMF establish mycorrhizal associations with wheat roots, they can contribute to various aspects of crop protection and resilience [63,64]. These fungi are used in agricultural practices through AMF inoculation to promote healthier plant growth and reduce the need for chemical fertilizers [65].…”
Section: Biological Wheat Crop Protectionmentioning
confidence: 99%